EFEKTIVITAS METODE PRAKTIK IBADAH DALAM PEMBELAJARAN FIQH PADA SISWA MADRASAH TSANAWIYAH - Salbiyah; Sudianto (JIP: Jurnal Ilmu Pendidikan, 2026)
This study aims to analyze the effectiveness of the worship practice method in improving students’ learning outcomes in Fiqh learning at the Madrasah Tsanawiyah (MTs) level. Fiqh learning, which is practical in nature, requires an approach that emphasizes not only cognitive aspects but also psychomotor and affective aspects. This research employed a quantitative approach with a pre-experimental design in the form of a one group pre-test and post-test. The research subjects were eighth-grade students at one MTs. Data were collected through tests, observation, and documentation. The results indicated a significant improvement between pre-test and post-test scores. The N-gain calculation showed a moderate to high improvement category. In addition, students demonstrated increased practical skills, activeness, and self-confidence in performing worship practices. These findings indicate that the worship practice method is effective in improving students’ understanding and practical skills in Fiqh learning.